2017
DOI: 10.1126/science.aao1309
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “The extent of forest in dryland biomes”

Abstract: Bastin (Reports, 12 May 2017, p. 635) infer forest as more globally extensive than previously estimated using tree cover data. However, their forest definition does not reflect ecosystem function or biotic composition. These structural and climatic definitions inflate forest estimates across the tropics and undermine conservation goals, leading to inappropriate management policies and practices in tropical grassy ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 15 publications
(26 reference statements)
1
41
0
Order By: Relevance
“…At the current time, these habitats are managed under a blanket policy of fire exclusion and suppression and fire-setting is a punishable offense according to the Indian Forest Act (Ratnam et al, 2016;Thekaekara et al, 2017). These policies, which stem from a historical misreading of these ecosystems as "forests" are inimical to the conservation and sustainable management of these savannas (Lehmann and Parr, 2016;Griffith et al, 2017). First, the notion that fires are always undesirable disturbances in these ecosystems, widespread amongst both managers and vegetation scholars, prevents nuanced understanding, and appropriate research on the ecology of these systems.…”
Section: Discussionmentioning
confidence: 99%
“…At the current time, these habitats are managed under a blanket policy of fire exclusion and suppression and fire-setting is a punishable offense according to the Indian Forest Act (Ratnam et al, 2016;Thekaekara et al, 2017). These policies, which stem from a historical misreading of these ecosystems as "forests" are inimical to the conservation and sustainable management of these savannas (Lehmann and Parr, 2016;Griffith et al, 2017). First, the notion that fires are always undesirable disturbances in these ecosystems, widespread amongst both managers and vegetation scholars, prevents nuanced understanding, and appropriate research on the ecology of these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Global initiatives could greatly benefit from CNNs, such as those recently implemented by the United Nations Food and Agricultural Organization ( [60]) to estimate the overall extension of forests in drylands biomes, where they used the collaborative work of hundreds of people that visually explored hundreds of VHR images available from Google Earth to detect the presence of forests in drylands. The uncertainties in such initiatives ( [61,63,64] could be decreased following our approach to build a CNN-based tree mapper). CNN-based tree and shrub detectors could serve to produce global characterizations of ecosystem structure and population abundance as part of the satellite remote sensing essential biodiversity variables initiative ( [65]).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of capturing the photosynthetic physiologies of C 3 and C 4 grass types, and their variation with CO 2 and climate, has long been recognized (Collatz, Berry, & Clark, ; Sellers et al, ; Still, Berry, et al, ). However, additional ecological and hydrological factors control C 3 and C 4 distributions and can interact in complex ways, producing offsetting effects driven by interactions with hydrological cycles (Griffith, Lehmann, et al, ) or by driving systems towards deterministically woody states (Bond, ; Moncrieff, Scheiter, Bond, & Higgins, ; Oliveras & Malhi, ). For example, in an experimental study conducted in a semi‐arid, mixed C 3 /C 4 grassland in North America, Morgan et al () showed that C 4 grasses were counterintuitively outperforming C 3 grasses owing to increases in water‐use efficiency driven by interacting effects of higher CO 2 and warming on soil moisture and plant physiological responses.…”
Section: Discussionmentioning
confidence: 99%